2020
DOI: 10.21203/rs.2.24724/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vitro virucidal activity of Echinaforce®, an Echinacea purpurea preparation, against coronaviruses, including common cold coronavirus 229E and SARS-CoV-2

Abstract: Background: Coronaviruses (CoVs) were long thought to only cause mild respiratory and gastrointestinal symptoms in humans but outbreaks of Middle Eastern Respiratory Syndrome (MERS)-CoV, Severe Acute Respiratory Syndrome (SARS)-CoV, and the recently identified SARS-CoV-2 have cemented their zoonotic potential and their capacity to cause serious morbidity and mortality, with case fatality rates ranging from 4 to 35%. Currently, no specific prophylaxis or treatment is available for CoV infections.Therefore we in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 25 publications
(35 reference statements)
0
15
0
2
Order By: Relevance
“…This includes a focus on new candidates. Apart from the candidates identified in this review, other molecules cited in the published literature and in the media as possible prophylactic candidates include existing herbal extracts such as Echinacea [39,40], nicotine [41] and new molecules including PAC-MAN (prophylactic antiviral CRISPR in human) for viral inhibition [42] and DARPin as well as multitarget binding neutralizing proteins [43]. The underrepresentation of new molecules in ongoing RCTs is likely in part due to the relative novelty of this virus and the necessary time lag to develop new molecules before testing them in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…This includes a focus on new candidates. Apart from the candidates identified in this review, other molecules cited in the published literature and in the media as possible prophylactic candidates include existing herbal extracts such as Echinacea [39,40], nicotine [41] and new molecules including PAC-MAN (prophylactic antiviral CRISPR in human) for viral inhibition [42] and DARPin as well as multitarget binding neutralizing proteins [43]. The underrepresentation of new molecules in ongoing RCTs is likely in part due to the relative novelty of this virus and the necessary time lag to develop new molecules before testing them in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…The coronaviruses are not new with seven already identified to be infectious to human. We are living and continuously adapting to coronaviruses HCoV-229E, HCoV-OC43, HCoV-NL63 and HCoV-HKU1, which causes the common cold (Signer et al, 2020). We have endured through two pandemics related to coronaviruses, with SARs-CoV identified in 2002 as the cause of severe acute respiratory syndrome (SARS) and MERS-CoV identified in 2012 as the cause of Middle East respiratory syndrome (MERS) (Paules et al, 2020).…”
Section: Problem Statementmentioning
confidence: 99%
“…In in vitro studies on cell lines it was observed that the antiviral effect of Echinacea extracts is limited only to the phases before the virus enters the host cell. The putative mechanism of action of the extracts is based on the interaction with the structural proteins of the viral glycoprotein S or the membrane protein M; therefore, the extracts may play a significant role in protection against infection as prophylactic agents [60].…”
Section: Aaem Annals Of Agricultural and Environmental Medicinementioning
confidence: 99%